2023
DOI: 10.3390/plants12040761
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Selenium Nanoparticles in Inducing Disease Resistance against Spot Blotch Disease and Promoting Growth in Wheat under Biotic Stress

Abstract: In the present study, SeNPs were synthesized using Melia azedarach leaf extracts and investigated for growth promotion in wheat under the biotic stress of spot blotch disease. The phytosynthesized SeNPs were characterized using UV-visible spectroscopy, scanning electron microscopy (SEM), energy-dispersive X-ray (EDX), and Fourier-transformed infrared spectroscopy (FTIR). The in vitro efficacy of different concentrations of phytosynthesized SeNPs (i.e., 100 μg/mL, 150 μg/mL, 200 μg/mL, 250 μg/mL, and 300 μg/mL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 103 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…To prepare the samples, 1 g plant leaves was ground with 10 mL acetone and filtered three times. Absorbance was measured at wavelengths of 645.0, 652.0 and 663.0 nm 33 . The chlorophyll contents of the leaves were then calculated using the following formulae: Chlorophyllgoodbreak−a0.25em()italicChlgoodbreak−agoodbreak=12.7()A663goodbreak−2.7()A645. Chlorophyllgoodbreak−b0.25em()italicChlgoodbreak−bgoodbreak=22.9()A645goodbreak−4.7()A0.25em663. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To prepare the samples, 1 g plant leaves was ground with 10 mL acetone and filtered three times. Absorbance was measured at wavelengths of 645.0, 652.0 and 663.0 nm 33 . The chlorophyll contents of the leaves were then calculated using the following formulae: Chlorophyllgoodbreak−a0.25em()italicChlgoodbreak−agoodbreak=12.7()A663goodbreak−2.7()A645. Chlorophyllgoodbreak−b0.25em()italicChlgoodbreak−bgoodbreak=22.9()A645goodbreak−4.7()A0.25em663. …”
Section: Methodsmentioning
confidence: 99%
“…Absorbance was measured at wavelengths of 645.0, 652.0 and 663.0 nm. 33 The chlorophyll contents of the leaves were then calculated using the following formulae:…”
Section: Chlorophyll Content Determinationmentioning
confidence: 99%
“…The suggested mechanism of nano-Se for plant disease resistance involves enhancing the capacity of antioxidants, inducing the pathway of jasmonic acid, reducing the accumulation of ROS and H 2 O 2 , and promoting the pathways for phytohormones signaling [171,202,210]. Many studies have confirmed the role of nano-Se in inducing the resistance of crops to phytopathogens such as Botrytis cinerea in cucumber [211], spot blotch disease in wheat [212], Podosphaera xanthii in melon [210], Fusarium-induced wilt disease in lettuce [209], and Alternaria leaf spot disease in the common bean [53]. Along with the mitigation of stress, other benefits that have been reported due to nano-Se in farming include nano-biofortification [204,205], improving the quality and shelf life of harvested crops [213], and mitigation of abiotic stresses, including salinity [214], heavy metals [215], and drought [216].…”
Section: Seedling Productionmentioning
confidence: 99%
“…Melia azardica based selenium nanoparticles also showed marvelous antifungal potential against spot blotch disease of wheat. This biocompatible strategy controlled the disease incidence and showed that various levels of selenium nanoparticles enhance the plant growth by modifying its biochemical profile and control the fungal stress by disrupting the fungal cell . Bioinspired Chenopodium quinoa mediated cerium oxide nanoparticles showed strong antifungal potential against the fungal disease Ustilago tritici affecting wheat crop.…”
Section: Aflatoxin Detoxification Approachesmentioning
confidence: 99%